1980
DOI: 10.1128/jb.144.3.1168-1173.1980
|View full text |Cite
|
Sign up to set email alerts
|

Effects of penicillin on macromolecular synthesis and surface growth of a tolerant streptococcus as studied by computer reconstruction methods

Abstract: Strains of Streptococcus mutans are very susceptible to growth inhibition by benzylpenicillin, but are tolerant to lysis when exposed to even high concentrations of this drug. These properties enabled this study of S. mutans GS-5 surface growth and peptidoglycan, ribonucleic acid, protein, and deoxyribonucleic acid syntheses in the absence of osmotic stabilization. Inhibition of syntheses of peptidoglycan, ribonucleic acid, and protein was dose dependent. Synthesis of peptidoglycan was most susceptible. Substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Previous reports (1,(3)(4)(5) have indicated that strains of S. mutans are tolerant to the lytic effects of penicillin G at any concentration tested. The data presented here indicate that S. mutans cells treated with a concentration of penicillin G within a relatively narrow range, and only under certain conditions, do indeed demonstrate cellular lysis.…”
Section: Discussionmentioning
confidence: 84%
“…Previous reports (1,(3)(4)(5) have indicated that strains of S. mutans are tolerant to the lytic effects of penicillin G at any concentration tested. The data presented here indicate that S. mutans cells treated with a concentration of penicillin G within a relatively narrow range, and only under certain conditions, do indeed demonstrate cellular lysis.…”
Section: Discussionmentioning
confidence: 84%
“…It was interesting to find that, for penicillin G, the concentrations required to inhibit division at the time of onset of C were identical to the concentrations of pencillin G that failed to substantially inhibit surface growth, DNA, RNA, or protein synthesis (5). In contrast, cells treated with high concentrations of penicillin G exhibited inhibition of DNA, RNA, and protein synthe-sis, and cells appeared to be unable to increase their surface (5).…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, bacteria tolerant to the killing action of these antibiotics are useful tools for examining the effects of antibiotics on cell growth and division. In this study, we examined the effects of various inhibitors of cell wall biosynthesis on division of Streptococcus mutans GS-5, a bacterium previously found to be tolerant- (5). The method of analysis used in this study is based on the cell cycle age distribution of exponential-phase cells which is invariant (2).…”
mentioning
confidence: 99%
“…And finally, earlier work with oral streptococci had shown that S. mutans was tolerant to the effects of penicillin (9,21,27). Krai and Callaway (13) have shown that S. mutans GS-5, an organism previously thought to be tolerant to the lytic effects of penicillin (9,21,27) does indeed show penicillin-induced lysis (greater than 90%) under certain conditions. Concentration of penicillin, pH of the medium, and cell density were found to be the three factors critical to effect penicillin-induced cellular lysis.…”
mentioning
confidence: 96%